Effect of selected natural and synthetic substances on rabbit reproduction–A mini review. Issue 3 (20th September 2021) - Svoradová, Andrea; Baláži, Andrej; Chrenek, Peter
Abstract: Numerous natural and synthetic substances have effects on reproduction through several mechanisms. This review aims to summarize the impact of green tea (GT), yucca schidigera (YS) extract, curcuma longa (CL), adenosine 3′, 5′‐cyclic monophosphate (cAMP) and isobutyl‐1‐methyl‐xanthine (IBMX) stimulators on rabbit reproduction performance. To obtain a comprehensive overview of this topic, the keywords "reproduction, " "substances, " "spermatogenesis, " "embryogenesis, "hormonal profil", "green tea", "yucca schidigera" were searched in such databases as WOS and PubMed to obtain relevant information. Spermatozoa profile was positively effected by the GT and YS, however, cAMP inhibitors stimulated spermatozoa motility resulted in positive or negative effects depending on the doses. Similarly, embryogenesis and hormonal profile were positively influenced by the GT, YS, cAMP and IBMX in a proper administration dose. Further research is needed to improve current knowledge about these substances to identify potential effects on the other reproduction parameters. Furthermore, future studies should combine GT, YS and CL with different plant extracts to determine their effects on spermatozoa status, embryogenesis as well as hormonal profile as key outcomes. This review summarizes current knowledge about effect of natural and synthetic substances on rabbit reproduction.